Why Indonesia's garlic self-sufficiency program failed? - Zaini, Anas; Danasari, Idiatul Fitri (Asian Journal of Agriculture and Rural Development, 2025)
This research provides insights into the ongoing failure of Indonesia’s garlic self-sufficiency program. Despite the implementation of various initiatives, the program has consistently failed to achieve its objectives. The study was conducted in East Lombok Regency, one of the main centers for garlic development in Indonesia. Using the Exit, Voice, Loyalty, and Neglect (EVLN) model, the research uncovers the root causes of the program's failure from the farmers’ perspective. A total of 45 farmers participated as respondents, including importer partner farmers, government assistance recipients, and independent farmers. The findings reveal that most farmers are dissatisfied with the program’s implementation, causing them to take passive and destructive responses. This dissatisfaction is primarily due to the inadequate provision of production facilities both in terms of quantity, quality, and delivery timing. Furthermore, ineffective import quota arrangements in terms of quantity and timing have suppressed the selling price of garlic for farmers at harvest time, while production costs are relatively high, especially for quality seeds and fertilizers. To address these issues, the program must be improved by ensuring timely, sufficient, and high-quality support for production facilities. Moreover, more effective import quota management is essential to stabilize prices and ensure fair profits for garlic farmers.